Comparison of clinical manifestations, outcomes and cerebrospinal fluid findings between herpes simplex type 1 and type 2 central nervous system infections in adults. Issue 10 (5th July 2014) - Moon, Song Mi; Kim, Tark; Lee, Eun Mi; Kang, Joong Koo; Lee, Sang‐Ahm; Choi, Sang‐Ho
<x xml:space="preserve">Abstract</x> In previous reports on the viral causes of central nervous system (CNS) infections, it has been generally recognized that HSV‐1 is a major cause of encephalitis, while HSV‐2 is the predominant cause of aseptic meningitis in adults. To examine this matter, the clinical characteristics in the two types of HSV CNS infections were investigated. In a retrospective cohort study which included all adult patients (≥16 years) between January 1999 and December 2013 in a 2, 700‐bed tertiary care hospital, all the patients in whom PCR of the CSF for HSV was positive were identified. Ninety‐five patients with positive CSF PCR results for HSV were included, 21 with HSV‐1 and 74 with HSV‐2. Many patients with HSV‐1 had encephalitis (13/21, 61.9%), whereas most patients with HSV‐2 had meningitis (62/74, 83.8%). However, HSV‐1 and HSV‐2 accounted for similar proportion of patients with HSV encephalitis (13/25, 52.0% vs. 12/25, 48.0%). Neurological sequelae were more frequent among patients with HSV‐1 (9/21, 42.9% vs. 6/74, 8.1%; P = 0.001). The present study suggests that HSV‐2 is not only a major cause of aseptic meningitis, but also it may cause serious manifestation as HSV‐1 encephalitis in adults. J. Med. Virol. 86: 1766–1771, 2014. © 2014 Wiley Periodicals, Inc.